Peran Orang Tua Dalam Literasi Membaca Permulaan Siswa Kelas Rendah Sekolah Dasar Ana Maritim - Halimatus Sa’diyah; Tyasmiarni Citrawati (LPPM Politeknik Pratama, 2023)
This study aims to determine the role of parents in Literacy beginning Reading and the obstacles experienced by parents. This type of research is qualitative research. The research sample was 16 parents. Retrieval of data using interview techniques, observation, and documentation. The results found by researchers are, 1) The role of parents in Literacy beginning Reading efforts, namely parents as educators, parents as role models, parents as facilitators, parents as motivators, parents as friends, parents as reward givers 2) Obstacles What is experienced by parents is that parents do not have much time with their children, parents do not provide a study space, lack of reading resources, and parents do not know how to start reading.